Higher Order Thinking Skills on Plant Germination Material - Wilda Rizkiyahnur Nasution (Institut Agama Islam Negeri, 2023)
Natural Science is knowledge of nature and its contents obtained through scientific means and scientific attitudes. One of the natural sciences that places more emphasis on concepts that occur in everyday life and the surrounding environment is biology. The application of biological sciences can be realized well if you have a deep conceptual understanding. Biology subject matter that requires students' ability to find facts, concepts. The method used in this research is research and development (RD). this research was adapted from the development model used is the 4D development model (Define, Design, Develop, and Disseminate). However, this research only reached the develop stage. The population in this study were all semester III students of Syekh Ali Hasan Ahmad Addary Padangsidempuan State Islamic University with a sample of 24 students in the 2022/2023 academic year. The following is an explanation of each stage of the development model.